The role of Specialized banks in financing Small and Medium Enterprises (SMEs) in Libya- case study (Development Bank in Murzuk) - Eqbal Alshami & Khalid Abdesamed (Journal of Pure & Applied Sciences, 2018)
Small and Medium Enterprises (SMEs) are important sectors due to its role for economic development in both developed and developing countries .The purpose of study is to know the extent to which the Development Bank has contributed to the financing SMEs in the Murzuk region. Results indicate that, lack of conformity of the needs of the region with the services and products that meet their needs, their resources and the quality of the funded projects. Projects that are economically infeasibility and incompatible with the needs of the region have been financed which could have been employed more efficiently and effectively in the economic development of the region. The study concluded with a number of recommendations, the most important being the granting of loans for projects of economic feasibility, which meet the needs of the region and directed towards the production of real goods to ensure better investment of financial resources. Develop a system and a specific mechanism to follow up and collect loan installments on time.